2014
DOI: 10.1097/aog.0000000000000118
|View full text |Cite
|
Sign up to set email alerts
|

First-Trimester Risk Factors for Preeclampsia Development in Women Initiating Aspirin by 16 Weeks of Gestation

Abstract: Women who develop preeclampsia while taking aspirin prophylaxis are more likely to have elevated first-trimester blood pressures. Conversely, first-trimester normotension is associated with a reduced risk of preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 20 publications
0
39
0
1
Order By: Relevance
“…Aspirin prophylaxis has to be initiated by 16 weeks' gestation to reduce significantly the risk of subsequent pre‐eclampsia or delivery of a SGA infant. It has been shown previously that, even in women receiving first‐trimester aspirin, maternal characteristics, such as higher blood pressure or BMI, on a single occasion in the first trimester lead to failure of aspirin prophylaxis. In this longitudinal study of women initiating aspirin in the first trimester, we were able to show that the development of pre‐eclampsia is related to higher blood‐pressure values from the beginning of pregnancy.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Aspirin prophylaxis has to be initiated by 16 weeks' gestation to reduce significantly the risk of subsequent pre‐eclampsia or delivery of a SGA infant. It has been shown previously that, even in women receiving first‐trimester aspirin, maternal characteristics, such as higher blood pressure or BMI, on a single occasion in the first trimester lead to failure of aspirin prophylaxis. In this longitudinal study of women initiating aspirin in the first trimester, we were able to show that the development of pre‐eclampsia is related to higher blood‐pressure values from the beginning of pregnancy.…”
Section: Discussionmentioning
confidence: 65%
“…However, even in patients initiating prophylaxis by 16 weeks, the residual prevalence of pre‐eclampsia may be as high as 9.3%, indicating that not all predisposing risks are mitigated. We have shown previously that, in women receiving prophylactic aspirin, higher blood pressure measured on a single occasion between 11 and 14 weeks is associated with an increased risk for pre‐eclampsia. To clarify if this association is related to a single observation in the first trimester or sustained blood‐pressure trends across all trimesters requires that serial blood‐pressure observations be made through pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Scholten and colleagues studied a large cohort of women with prior PE and found that 60% had a cardiovascular risk profile and 10–20% had metabolic syndrome, thrombophilia or hyperhomocysteinemia. We have recently shown that a cardiovascular risk profile (such as a history of hypertension or blood pressure in the prehypertension/hypertension range) is an important mediator of recurrent PE or failure of aspirin prophylaxis in our patient population. In the development of our multimarker algorithm, only a history of hypertension, PE, prior diabetes, mean arterial blood pressure and PAPP‐A MoM emerged as independent risk factors for PE.…”
Section: Discussionmentioning
confidence: 98%
“…However, even with the application of a multifactorial approach, prediction diverges considerably, ranging between 46.7% and 100% for PE requiring delivery before 34 weeks and between 29.4% and 71.1% for later‐onset PE. Potential explanations for this divergence include variation in population risk profiles , , utilization of low‐dose aspirin, statistical approaches to model development , or limited external validity of these algorithms. It is important to ascertain external validity of screening algorithms before their widespread clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…However, ongoing research is needed to determine whether a woman's country of origin can enhance how we screen for 23, 24 and attempt to prevent preeclampsia—especially preterm onset of preeclampsia. 25 Although we identified some immigrant groups at higher risk of preeclampsia in Ontario, other nationalities may be associated with a higher risk in other high immigration settings.…”
Section: Discussionmentioning
confidence: 99%